2022
DOI: 10.1097/ans.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Philanthropic Foundations' Discourse and Nursing's Future

Abstract: In this article, we examine external agents' effect on nursing's professional evolution and the consequences for the discipline's collective agency, social contract, and self-regulation. Situated within Foucault's theories of power, we review how the power of organizations reaches into the fabric of everyday life and explore how philanthropic foundations have influenced a diverse array of disciplines, including nursing. Through a genealogic lens, we examine nursing history and professionalization and conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As pointed out in part I, 2 genealogy, with its focus on relationships of power, builds upon what archaeology reveals. In this instance, our findings revealed that nursing's agency was thwarted through discursive practices across FON initiatives in 2 ways: (1) reduction in the overall number of nurses as invited speakers relative to speakers from other disciplines, and (2) minimizing nursing's collective voice as a function of the compressed speaking time for professional nursing organizations' representatives.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As pointed out in part I, 2 genealogy, with its focus on relationships of power, builds upon what archaeology reveals. In this instance, our findings revealed that nursing's agency was thwarted through discursive practices across FON initiatives in 2 ways: (1) reduction in the overall number of nurses as invited speakers relative to speakers from other disciplines, and (2) minimizing nursing's collective voice as a function of the compressed speaking time for professional nursing organizations' representatives.…”
Section: Discussionmentioning
confidence: 99%
“…This was largely due to speakers representing nursing organizations either being positioned in invited presentation slots with less presentation time (most often between 3.5 and 5 minutes each, compared with several invited speaker slots allowing 20-30 minutes per speaker) or having to compete for time in the public speaker sphere (limited to 2 minutes per speaker)40,41 (see Table 2). As argued in part I,2 nursing organizations serve as primary sources of collective agency for the discipline 2. When nursing's professional organizations' voices are limited, there are consequences for how, or even if, nursing is exercising collective agency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations